A Three-Dimensional Finite Element Model for Biomechanical Analysis of the Hip - Guang-Xing Chen; Liu Yang; Kai Li; Rui He; Bin Yang; Yan Zhan; Zhi-Jun Wang; Bing-Nin Yu; Zhe Jian (Cell Biochemistry and Biophysics, 2013)

Vulcaniibacterium tengchongense gen. nov., sp. nov. isolated from a geothermally heated soil sample, and reclassification of Lysobacter thermophilus Wei et al. 2012 as Vulcaniibacterium thermophilum comb. nov. - Tian-Tian Yu; En-Min Zhou; Yi-Rui Yin; Ji-Cheng Yao; Hong Ming; Lei Dong; Shuai Li; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Integrated application of 3D seismic and microseismic data in the development of tight gas reservoirs - Rui-Zhao Yang; Zheng-Guang Zhao; Wei-Jun Peng; Yu-Bo Gu; Zhan-Gang Wang; Xi-Qin Zhuang (Applied Geophysics, 2013)

Comparative study of the interactions between ovalbumin and three alkaloids by spectrofluorimetry - Rui-qiang Wang; Yu-jing Yin; Hua Li; Yi Wang; Juan-Juan Pu; Rui Wang; Huan-jing Dou; Chuan-jun Song; Rui-yong Wang (Molecular Biology Reports, 2013)

Thermus tengchongensis sp. nov., isolated from a geothermally heated soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Ji-Cheng Yao; Hong Ming; Yi-Rui Yin; En-Min Zhou; Min-Jiao Liu; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .